Công bằng phân phối, sự gắn kết và ý định tiếp tục công việc của các nhân viên giao hàng công nghệ tại Việt Nam - Nguyễn Thị Mỹ, Nguyệt; Vũ Tuấn, Dương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Based on the Social Exchange Theory and Job Embeddedness Theory, the author hypothesize that the distributive justice has an effect on a technology shipper’s intention to continue participation and the role of job embeddedness of technology shippers. Survey data from 192 technology shippers were analyzed using PLS-SEM, the results show distributive justice has a positive influence on job embeddedness. In addition, it was also found that distributive justice did not show a direct impact on continuous participation but it has a positive effect on technology shippers’ intention to continue working via job embeddedness. The findings provide knowledge on factors that motivate the continued participation of workers on online applications.